KARAKTERISTIK SERAT KAYU HIBRID Acacia auriculiformis x Acacia mangium SEBAGAI BAHAN BAKU PULP - Sri Sunarti; Harry Praptoyo; Arif Nirsatmanto (Center for Forest Biotechnology and Tree Improvement (CFBTI), 2016)
Acacia auriculiformis x Acacia mangium hybrid (Aa x Am) is a promising Acacia hybrid for pulp. Wood properties of the hybrid have been reported for their physical and chemical characteristics, but the fiber characteristics have not been investigated. This study was aimed to investigate the fiber characteristics of the hybrid. Wood samples were collected from three years old of Aa x Am hybrid trees planted in a hybrid seed orchard. For comparison, wood sample from other three species: A. mangium x A. auriculiformis hybrid (Am x Aa), A. mangium and A. auriculformis on the same age, planted in the orchard were also collected. The wood sample was prepared from a slice which was put into a bottle containing a combination of acetic acid and hydrogen peroxide (perhidrol) in 1:20 (v/v) for observing fiber characteristics. The results showed that in general the fiber characteristics of Aa x Am hybrid were comparable to those of three comparison species. The average fiber dimensions were intermediate between the two parents: 0.85 mm, 16.09 μm, 12.56 μm and 1.7 μm for fiber length, fiber diameter, fiber lumen width and fiber wall thickness, respectively. The derived values were variable to three comparison species, with the Muhlstep ratio and flexibility coefficient were slightly lower than those observed in Am x Aa hybrid. Based on the level of fiber quality for pulp, the Aa x Am hybrid was classified as level II, the same level as A. mangium and hybrid Am x Aa.